How Vertical Drains can minimize seasonal waterlogging in Bihar - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In this interview with Shanmugam Prathapar, Theme Leader, IWMI, we learn about how vertical drains can minimise seasonal water logging in Bihar. In Bihar, over 10.5% of its irrigated area is waterlogged. Water logging prevents early planting of wheat, and reduces yields. Vertical drains can minimise this problem while also recharging aquifers to meet irrigation demands in dry seasons. This study, implemented by IWMI scientists and supported by CCAFS, is being undertaken in Mukundpur, Vaishalli District, Bihar, India.